2016
DOI: 10.1016/j.tet.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Base-controlled 1,6-enyne-bicyclization: divergent synthesis of benzo[b]fluorenones and benzo[b]fluorenols

Abstract: An interesting base-controlled protocol for the divergent and atom-economic synthesis of benzo[b]fluorenones and benzo[b]fluorenols with the great diversity in substitution patterns has been developed. Started from readily available 1,6-enynes, good to excellent yields of the corresponding tetracyclic benzo[b]fluorenones and benzo[b]fluorenols can be chemoselectively achieved under metal-free conditions. Notably, only K2CO3 or Et3N was required as the promoter here and the reaction can work well in a high-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Indeed, addition of the quinone 4 raised the yield of 2 to 90% from 48%. It should be noted that parallel to our investigation the base‐promoted transformation of 1 and of related keto‐enynes was reported to yield the benzofluorenones in good yield …”
Section: Resultssupporting
confidence: 65%
“…Indeed, addition of the quinone 4 raised the yield of 2 to 90% from 48%. It should be noted that parallel to our investigation the base‐promoted transformation of 1 and of related keto‐enynes was reported to yield the benzofluorenones in good yield …”
Section: Resultssupporting
confidence: 65%
“…Our initial investigations focused on the cascade cyclization of 1,6-enynes 1a with K 2 S for reaction condition optimization using different catalysts, bases and solvents (Table ). First, the reaction between 1,6-enynes 1a and K 2 S was conducted with 20 mol % CuCl 2 and 3.0 equiv of Cs 2 CO 3 at 120 °C under an argon atmosphere in N , N -dimethylformamide (DMF) for 24 h. This set of conditions gave the desired product 2a in a 35% yield, but with an intramolecular cycloaddition product 3a in a 50% yield (entry 1). To improve the yield of 2a , a series of different bases, including K 2 CO 3 , Et 3 N, Bu 3 N, t -BuOLi, and diisopropylamine (DIPA), were then evaluated (entries 2–6), and the results showed that DIPA was proven to be most effective for this transformation, affording a 67% chemical yield of 2a (entry 6).…”
Section: Resultsmentioning
confidence: 89%
“…Recently Tu et al described a thermal intramolecular Diels-Alder reaction starting from 1,6-enynes (Scheme 28). [65] The adduct is assumed to undergo 1,5 proton transfer leading to the fluorenol intermediate which subsequently converts into the expected fluorenone though a base-promoted oxidation.…”
Section: Extended Fluorenones Through the Joint Construction Of Rings A And Cmentioning
confidence: 99%